Analisis Kesulitan Belajar Matematika serta Upaya Menanganinya pada Siswa Kelas I SDN Banyuajuh 9 Bangkalan - Candra Mahardika; Agung Setyawan (HMPS PGMI FTIK IAIN Jember, 2020)
This study aims to describe: 1) Materials that are considered difficult in mathematics in Even Semester, 2) Characteristics of mathematics learning difficulties experienced by students in class I, 3) Factors that cause learning difficulties, 4) Teachers' efforts in dealing with mathematics learning difficulties. This type of research is qualitative research. The informants in this study were class I students who had difficulty learning mathematics and also a class I teachers in SDN Banyuajuh 9. Data collection techniques used were observation, interviews, and documentation. Data were analyzed through steps of data reduction, data presentation, and drawing conclusions. The data validity checking technique is done by triangulating sources and techniques. The results showed that: 1) Material in mathematics that was considered difficult was the addition and subtraction of two-digit numbers, 2) Its characteristics were visual impairment and difficulty in language and reading, 3) Factors affecting students included interest and motivation to learn low mathematics and lack of mathematics learning media used by teachers, 4) Efforts made by teachers include providing group study guidance, asking smart students to help teach students who have difficulty learning mathematics, carrying out remedial tests, giving additional assignments and giving learning media so that students' learning processes are more concrete. Penelitian ini bertujuan untuk mendiskripsikan: 1) Materi yang dianggap sulit pada mata pelajaran matematika Semester Genap, 2) Karakteristik kesulitan belajar matematika yang dialami siswa kelas I, 3) Faktor penyebab kesulitan belajar, 4) Upaya guru dalam menangani kesulitan belajar matematika. Jenis penelitian ini adalah penelitian kualitatif. Informan dalam penelitian ini adalah siswa kelas I yang mengalami kesulitan belajar matematika dan juga guru kelas I di UPTD SDN Banyuajuh 9. Teknik pengumpulan data yang digunakan adalah observasi, wawancara dan dokumentasi. Data dianalisis melalui langkah-langkah reduksi data, penyajian data, dan penarikan kesimpulan. Teknik pemeriksaan keabsahan data dilakukan dengan triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa: 1) Materi pada mata pelajaran matematika yang dianggap sulit yaitu penjumlahan dan pengurangan bersusun dua angka, 2) Karakteristiknya yaitu adanya gangguan persepsi visual dan kesulitan dalam bahasa dan membaca, 3) Faktor yang mempengaruhi siswa antara lain minat dan motivasi belajar matematika yang rendah dan kurangnya media pembelajaran matematika yang dipakai oleh guru, 4) Upaya yang dilakukan guru antara lain memberikan bimbingan belajar secara berkelompok, meminta siswa yang pandai untuk membantu mengajari siswa yang mengalami kesulitan belajar matematika, melaksanakan tes remidi, memberikan tambahan tugas dan memberikan media pembelajaran agar proses belajar siswa lebih konkret. Kata Kunci: karakteristik, kesulitan belajar, Matematika